Construction management - Halpin, Daniel W.; Woodhead, Ronald W. (New York : John Wiley and Sons, 1998)
This book introduces to the basic topics which structure the complex business of developing and constructing a major facility or structure. The analogy of construction management being like the multifaceted challenges confronted by the decathalon athlete still holds up...
Keywords: Management; United States; Construction industry; Construction industry -- United States -- Management; Construction industry -- Law and legislation -- United States